THERMODYNAMICS OF REAL MINERAL CRYSTALS: EQUILIBRIUM CRYSTAL SHAPE AND PHASE SIZE EFFECT - Tauson V.L.; Abramovich M.G.; Akimov V.V.; Scherbakov V.A. (My University, 1993)
A thermodynamic explanation for the phase size effect in mineral systems containing small crystal particles is given using the equilibrium shape of the real crystal concept. The equations obtained are in accordance with the results of the analysis based on the principles of the linear thermodynamics of irreversible processes. Several examples of mineralogical interest are given. Graphs for sphaleritewurtzite equilibrium and calcite-aragonite equilibrium are constructed showing the wide ranges in thermodynamic parameters under which the formation of wurtzite and aragonite is possible. The location of the critical point in a binary solid system and values of the solubility of components are also found to be size dependent. In the ZnS-HgS system, the critical temperature rises for the small crystals compared with that for the bulk phases. The data obtained indicate the possibility of quantitative analysis of micromineral equilibria.